High Altitude Pulmonary Physiology - Oea Khairsyaf; Afriani; Erika Putri Rozita (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
High altitude is defined as regions above 2400 meters above sea level. Almost 2% of the world’s population dwells in high-altitude regions of the world. The respiratory system plays an important role in determining survival and undergoes a series of adaptive changes to compensate for hypobaric hypoxic states (decreased barometric pressure with increasing altitude) including increased alveolar ventilation, diffusion capacity, pulmonary vascular vasoconstriction, increased cardiac output, shifted of oxyhemoglobin dissociation curve and polycythemia. Being at a high altitude suddenly without compensation can be bad and cause medical problems that will arise when at an altitude due to a decrease in PaO2 caused by a drop in barometric pressure.